Self‐harm as the first presentation of attention deficit hyperactivity disorder in adolescents. Issue 4 (3rd May 2021) - Ward, John Headley; Curran, Sarah
Abstract : Background: Self‐harm (SH) in adolescence has previously been shown to significantly overlap with both attention deficit hyperactivity disorder (ADHD) and emotional dysregulation (ED). Our objective as such was to investigate the relationship between self‐harm and ADHD in our population and consider its clinical relevance. Methods: This case series analysis examined 124 presentations of SH in 13‐ to 17 year‐olds to Accident and Emergency Departments in South West London (97F:27M). Strength and Difficulties Questionnaires (SDQs) were used to screen for ADHD/hyperactivity and ED, and scores were compared with reference data obtained from Meltzer et al. (1999, International Review of Psychiatry (Abingdon, England), 15, 185). Results: Mean SDQ ADHD/hyperactivity scores were significantly higher in our SH sample compared to reference data ( p  < .0001). Furthermore, significantly greater ED scores were found in our sample compared with the control reference data. Conclusion: Our findings contribute to the evidence for an important link between ADHD and clinical presentations of SH and suggest there to be value in screening girls presenting to A&E with self‐harm for ADHD. We speculate that ED plays a role in the evolution of SH in dysregulated ADHD. We recommend that clinicians assessing adolescents have self‐harmed to be aware of possible ADHD symptoms and screen as appropriate; however, future research examining the temporal association between ADHD, emotional dysregulation and self‐harm is required to establish causal direction.